2013
DOI: 10.1089/rej.2013.1452
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminse 2 and EGGL, the Protein Cross-Link Formed by Transglutaminse 2, As Therapeutic Targets for Disabilities of Old Age

Abstract: Aging of the extracellular matrix (ECM), the protein matrix that surrounds and penetrates the tissues and binds the body together, contributes significantly to functional aging of tissues. ECM proteins become increasingly cross-linked with age, and this cross-linking is probably important in the decline of the ECM's function. This article reviews the role of ε-(γ-glutamyl)-lysine (EGGL), a cross-link formed by transglutaminase enzymes, and particularly the widely expressed isozyme transglutaminase 2 (TG2), in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 286 publications
(301 reference statements)
0
11
0
Order By: Relevance
“…TG2 activity is associated with arterial stiffening in humans and rats. TG2 forms glutamine-lysine cross-links between variety of extracellular proteins, including collagen and elastin [ 62 ]. TG2 is secreted through a Golgi-independent mechanism to the ECM, where it can be activated to a Ca 2+ -bound open conformation to catalyze the formation of isopeptide bonds [ 61 ].…”
Section: Mechanisms Connecting Mgd and Arterial Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…TG2 activity is associated with arterial stiffening in humans and rats. TG2 forms glutamine-lysine cross-links between variety of extracellular proteins, including collagen and elastin [ 62 ]. TG2 is secreted through a Golgi-independent mechanism to the ECM, where it can be activated to a Ca 2+ -bound open conformation to catalyze the formation of isopeptide bonds [ 61 ].…”
Section: Mechanisms Connecting Mgd and Arterial Hypertensionmentioning
confidence: 99%
“…TG2 is secreted through a Golgi-independent mechanism to the ECM, where it can be activated to a Ca 2+ -bound open conformation to catalyze the formation of isopeptide bonds [ 61 ]. Thus, Ca 2+ may be limiting TG2 activity in the ECM [ 62 ]. TG2 is activated by Ca 2+ , and inhibited by Mg 2+ [ 63 ].…”
Section: Mechanisms Connecting Mgd and Arterial Hypertensionmentioning
confidence: 99%
“…Although accelerated in diabetes, this process occurs throughout the life span in all human tissues, and a method for breaking existing cross-links is expected to be an essential component of a comprehensive rejuvenation program. 24 (The solutions evolved by hyper-thermophilic microbes to repair early stages in the glycation process before long-lived cross-links form at all 25 might also be employed prophylactically to reduce the rate of accumulation.) The identification in this study of a number of pathological phenomena that correlate specifically with stiffness, particularly increased angiogenic branching and impaired barrier function, will lend further support to the still-neglected strategy of cross-link removal by emphasizing its relevance to the headline diseases of cancer and atherosclerosis.…”
Section: The Effects Of Three-dimensional Matrix Stiffening On Vasculmentioning
confidence: 99%
“…The consequences of TG2 deficiency in humans are unknown. However, it has been suggested that TG2-mediated cross-linking occurs predominantly in damaged or ageing human tissues [11]. Amongst affected tissues, TG2 is strongly expressed in human atherosclerotic plaques, where it may contribute to plaque stability.…”
Section: Introductionmentioning
confidence: 99%